Evaluating the Digital Transformation of Lottery Operation: A Case Study on the E-Lotto Applications Impact on the Philippine Charity Sweepstakes Office in Metro Manila - Roldan, Cynthia T.; Bergancia-Celebrado III, Fe T.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2024)
The introduction of digital platforms has reshaped consumer behavior in various industries, and the lottery sector is no exception. While traditional lottery sales have long been a primary revenue source for PCSO, the advent of E-Lotto provides a new, convenient avenue for lottery. This research aims to evaluate the impact of E-Lotto on the sales performance of the Philippine Charity Sweepstakes Office (PCSO) within the National Capital Region (NCR). Further, this study determines whether E-Lotto serves as a complementary or competing channel for traditional lottery ticket sales and explores the implications of this shift on PCSO’s overall sales strategy. Through a mixed-methods approach, quantitative data on NCR lottery sales were analyzed to identify trends and assess shifts between digital and physical lottery channels. Qualitative interviews with PCSO stakeholders provide additional insights into operational and marketing strategies surrounding E-Lotto implementation. Findings reveal that E-Lotto expanded PCSO’s reach, particularly among younger, urban-based customers who prefer the convenience of online platforms. However, there is evidence that E-Lotto may also cannibalize traditional sales, especially in areas with smartphones and internet penetration. This underscores the need for PCSO to balance digital and physical sales channels effectively to maximize revenue. Recommendations include targeted marketing efforts, enhancing the user experience, and integrating cross-promotions between traditional and E-Lotto channels. By addressing these factors, PCSO can leverage the benefits of E-Lotto without undermining its established sales network. This study’s insights contribute to the broader understanding of digital transformation in gaming public institutions and its implications for sustainable revenue growth.